Report of a cooperative venture between the China Medical University library and the medical library of McGill University. - Crawford, D S (1988)
In March/April 1986, the medical library at McGill University in Montreal, Canada signed a cooperative agreement with the China Medical University (CMU) Library in Shenyang, China. This paper analyzes the operations of the CMU library within the context of the Chinese system of medical education, health care delivery, and medical librarianship. The CMU library is described in terms of collections, cataloging procedures, filing, public services (reference, bibliographic instruction, circulation, copy service), interlibrary loans, networking, conservation of materials, and personnel. Some interesting comparisons are made between the two libraries with respect to holdings, services provided, and training of staff. The plans for future cooperation are outlined.